Молодежь Украины: структура ценностей, социальное самочувствие и морально-психологическое состояние в условиях тотальной аномии - Панина, Н. (Социология: теория, методы, маркетинг, 2000)
The article presents original conceptual model of value-normative regulation of social behavior of the people and peculiarity of a determination of their psychological statein conditions of stable and unstable society. The use of scales of social well-being, anomie, authoritarianism, cynicism, life satisfaction, anxiety, which have been included into the sociological monitoring enabled the author to analyze interrelations between level of social well-being, mental health, and political choice of Ukrainian youth. According to the results of survey, the differences between integral indices of the social well-being for various age groups are not significant. However the analysis of inner structure of the social well-being (structure values) makes it possible to see that every generation has its own problems related to the satisfaction of social needs.